Post colonoscopy colonic perforation with parietal abscess: a rare case report - Choudhury, Manoj K.; Baruah, Utpal; Azharuddin, S. K. M. (International Surgery Journal, 2021)
Colonoscopy is a common method of diagnosing colon and rectum illnesses. Complications from colonoscopy are rare. However, perforation is one of the most common problems observed. The incidence is 0.005-0.085 percent. Extraperitoneal and mixed postcolonoscopy colonic perforations are classified as intraperitoneal, extraperitoneal and both combined. Extraperitoneal perforation is rare and frequently accompanied with subcutaneous emphysema and retroperitoneal abscess. Contrast CT scan is the most effective diagnostic and therapy tool. A parietal abscess after colonoscopy is quite rare. Only one incidence of post-colonoscopy retroperitoneal colonic perforation with parietal abscess has been reported. An unusual case of colonic perforation after diagnostic colonoscopy was presented with a parietal abscess on the left iliac area. The patient, a 63-year-old diabetic male, had a diagnostic colonoscopy for intestinal irregularity. Afternoon severe ache over left iliac region brought patient to doctor. Nothing notable was discovered. So, they prescribed symptomatic drugs. Symptomatic medications were prescribed but without any relief. An abdominal contrast CT was recommended to him by his doctor after a few days. This retro muscular accumulation in the left transverses abdominis muscle communicated with the sigmoid colon. No signs of peritonitis or septicemia. Patient was stable. The aspirated fluid was sent for culture and sensitivity testing, and intravenous hydration and antibiotics were commenced. Patient tolerated conservative care. The subject was discharged in 2 weeks. Diagnosis and treatment of perforation are critical to recovery.